Femtosecond laser-assisted capsulotomy: histological comparison of four different laser platforms - Hengerer, Fritz; Auffarth, Gerd U.; Conrad-Hengerer, Ina (Journal of refractive surgery, 2017)
Purpose: To compare histological analyses of capsulotomies from different laser systems with regard to tissue alteration, laser spot formation, and energy settings. Methods: Four femtosecond laser platforms approved for cataract surgery were evaluated: LenSx (Alcon Laboratories, Inc., Fort Worth, TX), Catalys (Abbott Medical Optics, Santa Ana, CA), Victus (Tecnolas/Bausch & Lomb, Munich, Germany), and LensAR (Topcon, Gamagori, Japan). Ten human anterior lens capsulotomy disks from each laser system were analyzed: five by means of light microscopy and five by transmission electron microscopy (TEM). TEM was used especially to examine the cellular and stromal changes at the cutting edges. The cellular demarcation line was measured at 15 points along the rim and statistically compared with the findings from all laser platforms. Three capsules of each laser platform were prepared for TEM to evaluate the cellular and tissue edges of the laser cuttings. Results: All capsulotomies revealed a circular demarcation zone of different sizes along the cutting edges. Light microscopy showed a radial tissue damage of 36.0 ± 12.3 μm after Victus laser capsulotomy, 8.9 ± 2.9 μm after Catalys laser capsulotomy, 25.2 ± 5.6 μm after LensAR laser capsulotomy, and 39.8 ± 5.1 μm after LenSx laser capsulotomy. Differences between the damaged tissue zones correlated with the laser systems and their energy settings. Conclusions: The use of less energy and larger spot separation led to smaller collateral damaged tissue areas along the cutting edges. The aberrant laser spots along the cutting edge may result in weakening of the remaining tissue, thereby enhancing the risk for capsular ruptures during surgery.